2012
DOI: 10.3343/alm.2012.32.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peptide Nucleic Acid Probe-based Real-time PCR for Detection of Mycobacterium tuberculosis Complex and Nontuberculous Mycobacteria in Respiratory Specimens

Abstract: BackgroundA peptide nucleic acid (PNA) probe-based real-time PCR (PNAqPCR™ TB/NTM detection kit; PANAGENE, Korea) assay has been recently developed for the simultaneous detection of Mycobacterium tuberculosis complex (MTBC) and nontuberculous mycobacteria (NTM) in clinical specimens. The study was aimed at evaluation of the performance of PNA probe-based real-time PCR in respiratory specimens.MethodsTo evaluate potential cross-reactivity, the extracted DNA specimens from Mycobacterium species and non-mycobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Their second product, the PANA qPCR TB/NTM Detection kit, is a simple, one-stop kit which extracts the microbial DNA from several different clinical sample types and using standard qPCR methods, where the molecular beacon has been replaced with a PNA probe, enables the discrimination of TB from NTM in roughly 3 hours while achieving >99% specificity for both targets. However, in one study, sensitivity reached only 69% for NTM but overall, this kit demonstrated similar performance characteristics to other nucleic acid amplification-based assays (Choi et al, 2012). A more recent study comparing the Cobas TaqMan MTN assay (Roche Diagnostics) with Panagene's system found that the performance of the PNA-based assay is superior to the TaqMan assay (Kim et al, 2013).…”
Section: Artificial Probes and Diagnostic Clinical Microbiologymentioning
confidence: 88%
See 2 more Smart Citations
“…Their second product, the PANA qPCR TB/NTM Detection kit, is a simple, one-stop kit which extracts the microbial DNA from several different clinical sample types and using standard qPCR methods, where the molecular beacon has been replaced with a PNA probe, enables the discrimination of TB from NTM in roughly 3 hours while achieving >99% specificity for both targets. However, in one study, sensitivity reached only 69% for NTM but overall, this kit demonstrated similar performance characteristics to other nucleic acid amplification-based assays (Choi et al, 2012). A more recent study comparing the Cobas TaqMan MTN assay (Roche Diagnostics) with Panagene's system found that the performance of the PNA-based assay is superior to the TaqMan assay (Kim et al, 2013).…”
Section: Artificial Probes and Diagnostic Clinical Microbiologymentioning
confidence: 88%
“…Choi and co-workers developed a highly specific assay that utilised fluorescent PNAs to detect and discriminate among M. tuberculosis and non-tuberculous mycobacteria in clinical specimens. Application of the assay to 531 patient specimens, demonstrated no Type-I or Type-II errors and a specificity of 100% and 99.6%, for non-tuberculous Mycobacteria and M. tuberculosis, respectively (Choi et al, 2012). Though conceptually similar to standard real-time PCR-based approaches using molecular beacons, there are differences.…”
Section: Elongation Arrestmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the AFB stain yields poor positive predictive values for TB in clinical settings in which NTM is frequently isolated, because it does not allow differentiation MTB from NTM [5]. Recently, several investigators have used peptide nucleic acid (PNA) probes for the identification of MTB and NTM in various specimens, in- cluding cultures, sputum, and tissue [6][7][8][9][10][11][12]. PNA probes are artificially synthesized DNA analogues with an uncharged peptide backbone, which have more favorable hybridization properties and chemical, thermal, and biological stability than previous probes [13,14].…”
Section: Tuberculosis (Tb) Is Caused By Mycobacterium Tuberculosismentioning
confidence: 99%
“…A PNA probe-based real-time PCR assay has been developed for the diagnosis of mycobacterial infections, particularly for distinguishing between Mycobacterium tuberculosis and nontuberculous mycobacteria (NTM) in clinical specimens (13,14 T , and M. xenopi ATCC 19250 T ), were used in this study. All clinical isolates were collected from the Asan Medical Center (Seoul, Republic of Korea) during the period from January 2004 to June 2011.…”
mentioning
confidence: 99%